Use of Analytical Hierarchy Process (AHP) in Highway Alignment Planning in Nepal: An Expert Questionnaire Survey - Shrestha, Milan; Neupane, Shuva Raj; Mishra, Binaya Kumar (Himalayan Journal of Applied Science and Engineering, 2025)
Highway Alignment Planning is an important albeit most overlooked aspect of highway development in developing countries. More often than not, highway alignments are influenced by various issues which further complicate the planning process. In this study, an expert questionnaire survey is conducted to identify the weightage of multiple criteria themes that are deemed to affect highway alignment selection. For this study, various criteria such as Elevation (Altitude), Slope, Aspect, Soil type, Rock type, Land Use, Drainage Orders, Existing Roads, Agricultural area, Built-up area, water bodies in the locality, noise and air pollution, are considered which govern the highway alignments selection of the highway. These criteria are grouped into three respective themes i.e. Engineering, Economical, and Environment. A fourth theme is formed by combining the previous three themes. An AHP based on an Expert survey is conducted to assign weightage to each criterion in each theme and then to each theme in a combined theme. This study also involves determining the weightage of criteria that are used to evaluate multiple alignments generated by individual themes for multi-criteria analysis (MCA). The evaluation criteria identified are the length of the alignment, average slope, affected area of water bodies, affected Area of Agricultural Land, affected area of built-up area (i.e., Settlement Area), and affected area of the protected area. The study involved multiple experts from both academic and professional fields.